Comparing the Efficacy and Safety of Low-Carbohydrate Diets with Low-Fat Diets for Type 2 Diabetes Mellitus Patients: A Systematic Review and Meta-Analysis of Randomized Clinical Trials. (6th December 2021) - Li, Shunhua; Ding, Lu; Xiao, Xinhua
Abstract : Introduction . To compare the efficacy of low-carbohydrate diets (LCDs) with low-fat diets (LFDs) in body weight and glycemic control for type 2 diabetes mellitus (T2DM) patients, and their cardiovascular and renal safety. Methods . We searched PubMed, Ovid, Embase databases, Cochrane Central Register of Controlled Trials (CENTRAL), and ClinicalTrials.gov from inception to April, 2021. Randomized controlled trials (RCTs) which lasted more than 3 months were included. The primary outcomes are the mean change from baseline in glycated haemoglobin (HbA1c) and body weight loss. Secondary outcomes included mean difference in lipid parameters, blood pressures, and serum creatinine. Results . Totally, 12 RCTs met inclusion criteria representing 761 patients. Compared with LFDs, treatment with LCDs achieved significant reduced HbA1c by 0.35% (95% CI: −0.45, −0.24; P  < 0.00001). LCDs appeared to be more beneficial in decreasing body weight than LFDs (WMD = −2.99 kg; 95% CI: −4.36, −1.63; P  < 0.0001), especially in the subgroup that used VLCDs (WMD = −9.49 kg; 95% CI: −12.88, −6.09, P  < 0.00001). For cardiovascular risk factors, the LCD interventions significantly reduced TG concentration (WMD: −0.20 mmol/l; 95% CI: −0.31, −0.10; P  = 0.0001) and increased HDL-C concentration (WMD: 0.09 mmol/l; 95% CI: 0.05, 0.13; P  < 0.00001). Subgroup analyses demonstrated that the difference in HbA1c, TG, and HDL-C between two dietary restrictions respectively lasted up to 1.5 and 2 years, whereas the beneficial effects of body weight loss diminished over time and disappeared after 2 years. LCDs were not associated with decreased level of TC or LDL-C, neither SBP nor DBP in comparison with LFDs. Moreover, no significant difference in serum creatinine could be found among such two diet interventions. Conclusions . LCDs are superior to LFDs for T2DM patients in improving HbA1c and reducing body weight, with a rewarding effect of some cardiovascular risk factors in a longer-term diabetes management. However, available data are insufficient to evaluate the association between diet interventions and renal safety. Future larger longer-term follow-up clinical trials are needed to provide more evidence about the sustainable effects and safety of LCDs compared with LFDs.